2020
DOI: 10.1186/s40792-020-00959-x
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic transformation of thyroid cancer in mesentery metastases presenting as intestinal perforation: a case report

Abstract: Background Anaplastic thyroid carcinoma is a highly aggressive form of thyroid cancer associated with a very poor prognosis. Anaplastic transformation most commonly occurs in the thyroid itself or within regional lymph nodes. Here we report the case of a patient with papillary thyroid cancer, presenting with colon perforation as a result of anaplastic transformation of metastases in the mesentery tissue. There have been no previous reports of this form of anaplastic transformation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…4 Similar was followed in our case but the liver and abdominal nodal metastases are rare. Only a few such reports exist in the literature: (i) Meyer et al 5 reported pelvic nodal mass in insular carcinoma, while (ii) anaplastic transformation of papillary thyroid cancer in form of mesenteric mass was reported by Hosoda et al 6 ; but our case showed the unique observation of bilateral paraaortic nodal metastases in HCTC. As noted in this case, lack of adequate RAI concentration, a common observation in HCTCs precludes the use of powerful RAI therapy.…”
Section: Discussionmentioning
confidence: 57%
“…4 Similar was followed in our case but the liver and abdominal nodal metastases are rare. Only a few such reports exist in the literature: (i) Meyer et al 5 reported pelvic nodal mass in insular carcinoma, while (ii) anaplastic transformation of papillary thyroid cancer in form of mesenteric mass was reported by Hosoda et al 6 ; but our case showed the unique observation of bilateral paraaortic nodal metastases in HCTC. As noted in this case, lack of adequate RAI concentration, a common observation in HCTCs precludes the use of powerful RAI therapy.…”
Section: Discussionmentioning
confidence: 57%
“…Generally, symptomatic metastases of extraabdominal malignancies in the intestines are rare. Regarding small bowel metastasis of thyroid carcinoma, we found five references in the medical literature [15][16][17][18][19] -all are related to ATC, three of them presented with intestinal perforation, [17][18][19] as in our case. The most common primary tumors metastasizing to the small bowel are lung carcinomas and malignant melanoma, [43][44][45][46][47][48] followed by renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 87%
“…49,50 Rare cases of testicular seminoma, 51 osteosarcoma, 52,53 and Ewing sarcoma 54 have also been described. Symptoms of intestinal metastasis described in the literature include intussusception, 16,[20][21][22][23][24][25][26][27][28][29][43][44][45][46][47][48][49][50][51][52][53][54] and perforation [17][18][19][30][31][32][33][34][35][36][37][38][39][40][41][42] . The curative treatment of ATC is multimodal and consists of surgery and external beam radiation therapy with radio-sensitizing chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, a small subset of PTC and FTC cases transform into anaplastic carcinoma. Anaplastic transformation occurs within primary tumors [ 3 ], metastatic lymph nodes [ 4 ], and metastatic lesions in distant organs [ 5 ]. Patients with anaplastic transformation have a poor prognosis, with six-month survival rates of only 35% [ 6 ].…”
Section: Introductionmentioning
confidence: 99%